CdS/ZnIn2S4/TiO2 3D-heterostructures and their photoelectrochemical properties. (3rd June 2016) - Yin, Xuehua; Sheng, Pengtao; Zhong, Fenfen; Nguyen, VanManh; Cai, Qingyun; Grimes, Craig
Abstract : A CdS/ZnIn2 S4 /TiO2 3D-heterostructure with high photoconversion efficiency and photocatalytic activity was synthesized and applied. Abstract : We describe the synthesis and application of a three-dimensional (3D) CdS quantum dot/ZnIn2 S4 nanosheet/TiO2 nanotube array (CdS/ZnIn2 S4 /TiO2 ) heterostructured material architecture. TiO2 nanotube arrays (TiO2 NTAs) are used as the synthetic template, subsequently sensitized using hydrothermal and successive ion layer adsorption and reaction (SILAR) techniques. The described synthesis approach offers a powerful technique in the design of 3D heterostructure systems. Under AM1.5G illumination, the 3D CdS/ZnIn2 S4 /TiO2 samples generate a photocurrent of approximately 4.3 mA cm −2, with a photoconversion efficiency of 2%. Samples are tested for their ability to photocatalytically degrade target agents; it is noteworthy that after 90 min illumination 100% of 2, 4-dichlorophenoxyacetic acid (2, 4-D) is removed.